2012
DOI: 10.1002/anie.201204395
|View full text |Cite
|
Sign up to set email alerts
|

Gram‐Scale Synthesis of Nickel(II) Norcorrole: The Smallest Antiaromatic Porphyrinoid

Abstract: Small is beautiful: A ring-contracted sister of porphyrin, norcorrole, has been synthesized efficiently as a stable molecule by a nickel-templated strategy. The norcorrole complex is stable but exhibits a distinct antiaromatic character according to the Hückel rule. Oxidation of the norcorrole complex provides an aromatic oxacorrole complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
206
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 220 publications
(216 citation statements)
references
References 40 publications
(22 reference statements)
7
206
1
2
Order By: Relevance
“…NiNC exhibits five absorption bands at 259, 290, 428, 474, and 514 nm, respectively. They are very similar to the reported [12,23]. The maximum absorption is at 428 nm.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…NiNC exhibits five absorption bands at 259, 290, 428, 474, and 514 nm, respectively. They are very similar to the reported [12,23]. The maximum absorption is at 428 nm.…”
Section: Resultssupporting
confidence: 89%
“…Prior to use, it was purified by refluxing in concentrated nitric acid for 6 h, followed by centrifugation, resuspension and filtration and dried to evaporate the solvent. NiNC was synthesized as described in the literatures [12][13][14]. Uric acid (UA), ascorbic acid (AA) and dopamine (DA) were purchased from SigmaAldrich (http://www.sigmaaldrich.com).…”
Section: Experimental Instruments and Chemicalsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the bridging oxygen atom is sp 3 hybridized there appeared to be scope for an interaction between the ring moieties, since the lone pairs can interact significantly with the -system of the phenyl ring. For example, the recent spectroscopic characterization and theoretical analysis of a novel nickel 10-oxacorrole complex by Kobayashi and co-workers demonstrated that an sp 3 hybridized oxygen atom can form part of a cyclic -system with properties very similar to those of a conventional 18--electron heteroaromatic -system of a porphyrinoid ligand [19].…”
Section: Synthesis and Characterizationmentioning
confidence: 99%